2013
DOI: 10.5194/acp-13-5337-2013
|View full text |Cite
|
Sign up to set email alerts
|

Particle and gaseous emissions from individual diesel and CNG buses

Abstract: In this study size-resolved particle and gaseous emissions from 28 individual diesel-fuelled and 7 compressed natural gas (CNG)-fuelled buses, selected from an in-use bus fleet, were characterised for real-world dilution scenarios. The method used was based on using CO2 as a tracer of exhaust gas dilution. The particles were sampled by using an extractive sampling method and analysed with high time resolution instrumentation EEPS (10 Hz) and CO2 with a non-dispersive infrared gas analyser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 43 publications
5
42
2
Order By: Relevance
“…Total PN emissions of 1.4 × 10 14 p/km have been measured for DPF equipped buses and 6.5 × 10 14 p/km for non-DPF buses (see reviews of Morawska et al, 2008;Hallquist et al, 2013). The Euro V DPF equipped truck had emissions of 2 × 10 13 p/km which is lower but close to the reported value.…”
Section: Literature Overview On Spn Emission Levelssupporting
confidence: 55%
“…Total PN emissions of 1.4 × 10 14 p/km have been measured for DPF equipped buses and 6.5 × 10 14 p/km for non-DPF buses (see reviews of Morawska et al, 2008;Hallquist et al, 2013). The Euro V DPF equipped truck had emissions of 2 × 10 13 p/km which is lower but close to the reported value.…”
Section: Literature Overview On Spn Emission Levelssupporting
confidence: 55%
“…Two tests were performed: (1) acceleration from standstill to about 20 km/h, and (2) driving with a constant velocity of about 20 km/h. In the acceleration test CNG bus emitted lower mass rate of PM 10 , but on the other hand particle number was approximately 5 times higher [17]. Average NO x emissions were higher for the CNG buses compared to diesel buses.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Average NO x emissions were higher for the CNG buses compared to diesel buses. It was also reported that scatter of NO x emissions of the CNG buses was high, as it mainly correlates with the variability in vehicle maintenance and variation in the composition of the CNG fuel [17]. THC Energies 2018, 11, 2160 4 of 20 emissions were under detection limit of the applied measurement equipment for all buses and CO emissions were over detection limit only for six buses [17].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations